Language Style of AdvertisementsLanguage Style of Advertisements (e-Journal of Linguistics, 2023)
The article aims to find the type of language style and the meaningsimplied in the advertisement. The data were taken fromadvertisements in Now! Bali magazine was published from May 2018to June 2018. They were analyzed using the descriptive qualitativemethod and the theory type of language style (W. D. Wells, 2009),and the theory of meaning (Keraf, 2006). The result shows that thereare seven types of language styles applied in them including similes,personification, metonymy, alliteration, assonance, ellipsis, andhyperbole. In terms of meaning, denotative and connotativemeanings are implied.